Change agents’ cognitive maps of circular supply chain transition : An investigation of barriers, actions, and outcomes - Nyffenegger, Roger A.; Zehendner, Axel; Quarshie, Anne M.; Leuschner, Rudolf (Elsevier, 2025)
Integrating circular principles into supply chains (SCs) is a significant challenge for many managers aiming to decouple their organizations’ activities from the use of natural resources and environmental degradation. Despite increasing research focusing on the circular economy (CE), little attention has been given to individuals’ interpretations of the circular transition and their own transition strategies. This interpretivist qualitative study provides insights into the managerial sensemaking of the circular SC transition, including the barriers faced and the strategic actions taken to overcome the barriers and realize desired outcomes. Semi-structured interviews with 19 change agents were combined with a cognitive mapping approach. The individual cognitive structures were synthesized into an overarching sensemaking map that captured the informants’ perceptions and social construction of the circular SC transition. The findings reveal four shared cognitive frames (i.e., the most plausible schemes) held by change agents: (1) SC cooperation, (2) circular business models, (3) circular design, and (4) material choice. Moreover, we develop a framework that highlights how sensemaking contributes to the calibration of cognitive frames and the strategies pursued by individuals. We contribute to the literature by providing insights into change agents’ social construction and perceptions of the circular SC transition and propose key takeaways for practitioners and policymakers.